Improved hemophagocytic lymphohistiocytosis index predicts prognosis of adult Epstein-Barr virus-associated HLH patients - Shuyan Yao; Lingbo He; Ruoxi Zhang; Menghan Liu; Zhengjie Hua; Heshan Zou; Zhao Wang; Yini Wang (Annals of Medicine, 2023)
AbstractBackground Epstein-Barr virus (EBV)-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is a common subtype of HLH with heterogeneous clinical presentations from self-limited to death, of which adults are worse than children.Objective To establish predictors of mortality risk in adult EBV-HLH patients for timely and appropriate treatment.Methods Patients with confirmed EBV-HLH admitted to Beijing Friendship Hospital from January 2015 to December 2019 were enrolled and statistical analysis of their laboratory test results was performed.Results Among 246 adult patients with EBV-HLH, the deceased were older (p < 0.05), with fewer blood cells (p < 0.05), poorer renal function (p < 0.01), higher levels of procalcitonin (PCT) (p < 0.01), as well as soluble interleukin-2 receptor (sCD25) (p < 0.01). The overall median survival time of patients was 135 days, 87 days for patients without transplantation and 294 days with transplantation (p < 0.001). A combined index of sCD25, PCT, and estimated glomerular filtration rate (eGFR) was obtained to predict prognosis, named the Improved HLH index (IH index), and patients were divided into three groups meeting IH- (i.e. sCD25 ≤ 18,000 pg/mL, PCT ≤ 1.8 ng/mL, eGFR ≥ 90 mL/min/1.73m2), IH1+ (i.e. only sCD25 > 18,000 pg/mL or only eGFR < 90 mL/min/1.73m2), and IH2+ (i.e. the rest), respectively. In patients with the HScore ≥ 169 or meeting HLH-04, those meeting IH2+ had significantly worse prognoses than those who met IH1+ or IH- (p < 0.001). In the group meeting IH + or IH2+, patients who received allo-HSCT had better prognoses than those who did not (p < 0.05), but there was still a significant difference in prognosis among the three groups in transplanted patients (p < 0.001).Conclusion The IH index can early identify adult patients with a poor prognosis of EBV-HLH, initiating timely and appropriate treatment.KEY MESSAGESA combined index of sCD25, PCT, and eGFR was obtained to predict prognosis, named the Improved Hemophagocytic Lymphohistiocytosis index (IH index).IH index can early identify adult patients with a poor prognosis of EBV-HLH, initiating timely and appropriate treatment.